2016
DOI: 10.1038/jhg.2015.163
|View full text |Cite
|
Sign up to set email alerts
|

De novo missense mutations in NALCN cause developmental and intellectual impairment with hypotonia

Abstract: Three recessive mutations in the sodium leak channel, nonselective (NALCN) have been reported to cause intellectual disability and hypotonia. In addition, 14 de novo heterozygous mutations have been identified in 15 patients with arthrogryposis and neurodevelopmental impairment. Here, we report three patients with neurodevelopmental disease and hypotonia, harboring one recurrent (p.R1181Q) and two novel mutations (p.L312V and p.V1020F) occurring de novo in NALCN. Mutation p.L312 is located in the pore forming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…The detected variant of NALCN (c.1789G > A, p.V597I) with a de novo condition is strongly considered to be responsible for our patient's disease for the following four reasons. First, patients reported with mutations in NALCN have similar clinical features to our patient (3)(4)(5). Second, Sanger sequencing confirmed that the patient had this missense mutation, and that the unaffected parents and sister did not have (Fig.…”
Section: Letter To the Editorsupporting
confidence: 72%
See 2 more Smart Citations
“…The detected variant of NALCN (c.1789G > A, p.V597I) with a de novo condition is strongly considered to be responsible for our patient's disease for the following four reasons. First, patients reported with mutations in NALCN have similar clinical features to our patient (3)(4)(5). Second, Sanger sequencing confirmed that the patient had this missense mutation, and that the unaffected parents and sister did not have (Fig.…”
Section: Letter To the Editorsupporting
confidence: 72%
“…First, patients reported with mutations in NALCN have similar clinical features to our patient (3)(4)(5). Second, Sanger sequencing confirmed that the patient had this missense mutation, and that the unaffected parents and sister did not have (Fig.…”
Section: To the Editormentioning
confidence: 64%
See 1 more Smart Citation
“…For example, the 178 bp deletion in NALCN (a gene related with adductive thumbs) disrupted an ADE in the cerebellum and exhibited a sharp difference in enhancer activities between monkeys and apes ( Figure 5F and Table S26). It was reported that NALCN was also associated with neurodevelopmental diseases (Bramswig, et al 2018) and the mutation of NALCN leads to syndromic neurodevelopmental impairment (Fukai, et al 2016). Another example is the ASSV (242 bp deletion) within an ADE in PcGm in TLN2 ( Figure 5A), a brain-function-related gene (Gusareva, et al 2018;Mendez-David, et al 2017).…”
Section: Discussionmentioning
confidence: 98%
“…We first evaluated whether the deletion could unmask recessive alleles, and found no rare pathogenic mutations within the seven 16p12.1 genes on the non-deleted chromosome (Table S7) 55,85,86 . Further, in another family (family GL_011), a rare deletion in 2p16.3 inherited from a non-16p12.1 carrier parent, encompassing NRXN1, was also identified in a proband.…”
Section: Secondary Variants Account For Disease Expressivity In 16p12mentioning
confidence: 99%